Pemikiran Pierre Bourdieu dalam Memahami Realitas Sosial - Mega Mustikasari; Arlin Arlin; Syamsu A Kamaruddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to find out Bourdieu's thoughts, as an introduction to understanding social reality. This study introduces the basic ideas of Bourdieu's thinking in understanding how individuals relate to form